Gemcitabine Plus Cisplatin Chemotherapy Prolongs the Survival in Advanced Hilar Cholangiocarcinoma: A Large Multicenter Study. (June 2020) - Shin, Dong Woo; Kim, Min Jae; Lee, Jong-chan; Kim, Jaihwan; Woo, Sang Myung; Lee, Woo Jin; Lee, Kwang Hyuck; Hwang, Jin-Hyeok
Abstract : Objectives: Gemcitabine plus cisplatin (GC) is recommended as first-line treatment for advanced cholangiocarcinoma. We investigated the impact of GC in patients with unresectable hilar cholangiocarcinoma (HC) based on the time taken for effective biliary drainage (EBD). Materials and Methods: We retrospectively enrolled 113 patients with unresectable HC. Thirty-nine and 74 patients received GC chemotherapy and best supportive care (BSC), respectively. EBD was defined as a reduction in total bilirubin >50% or to a value <2 mg/dL after the drainage procedure. Early EBD (eEBD) and delayed EBD (dEBD) were separated by 2 weeks. Overall survival (OS) was estimated. Results: The GC group showed a significantly longer median OS than the BSC group (12.8 vs. 6.1 mo; P <0.001). Moreover, the eEBD group experienced a significantly longer OS than the dEBD group (8.2 vs. 4.3 mo; P <0.001). GC led to improved OS in the eEBD (12.8 vs. 6.8 mo; P =0.003) and dEBD (12.2 vs. 3.4 mo; P =0.009) groups. In multivariate analysis, dEBD (adjusted hazard ratio [aHR], 1.785; 95% confidence interval [CI], 1.183-2.691; P =0.006), BSC (aHR, 2.409; 95% CI, 1.579-3.675; P <0.001), and an ECOG status ≥2 (aHR, 3.721; 95% CI, 2.093-6.615; P <0.001) were associated with poor prognosis. In GC group, the older (70 y and above) patients did not have a higher risk of death than younger patients. Conclusions: GC prolongs the survival of patients with unresectable HC, even those with dEBD or elderly.